PENGARUH PERAWATAN PERIANAL DENGAN MINYAK KELAPA TERHADAP PENCEGAHAN TERJADINYA GANGGUAN INTEGRITAS JARINGAN KULIT PERIANAL PADA BAYI DIARE - Maftukhah, Anik (Akademi Keperawatan Pamenang, 2013)
Disintegrity perianal skin tissue is one of problem at diarrhea baby. It is a change wholeness perianal skin tissue that cause by diaper dermatitis or pants that contact with feces. This reseach aim to prove the influence of perianal treatment using coconut oil to prevention disintegrity perianal skin tissue at diarrhoe baby. This is quasy experimental study. The population is diarrhea baby that taken care in Gempol Primary Health Service. Sample is used by 36 responder teken by pursuant to criteria inclution. Demography data collected by kuesioner and to know integrity perianal skin tissue used observation sheet. Than analyse Based on statistical test using Mann Withney with significance level α <0,05. The result was found that the influence of perianal treatment with coconut oil to prevention disintegrity perianal skin tissue on diarrhoea baby with significance level of p= 0,001. Based analyse result, it can be conclude that perianal treatment use coconut oil can be prevent disintegrity perianal skinn tissue on diarrhea baby couse coconut oil is emolion that contain tokoferol, laurat acid and caprilat acid. Perianal treatment on diarrhea baby in early can be prevent disintegrity perianal skin tissue so it can not be irritation. Keyword : Perianal treatment, coconut oil, disintegrity perianal skin tissue.